Jump In! An Investigation of School Physical Activity Climate, and a Pilot Study Assessing the Acceptability and Feasibility of a Novel Tool to Increase Activity during Learning - Graham, Dan J.; Lucas-Thompson, Rachel G.; O’Donnell, Maeve B. (Frontiers in Public Health, 2014)
Physical activity (PA) benefits children’s physical and mental health and enhances academic performance. However, in many nations, PA time in school is decreasing under competing pressures for time during the school day. The present paper argues that PA should not be reduced or seen as incompatible with academic learning. Instead, the authors contend that it is critical to develop tools that incorporate PA into content learning during the school day. To facilitate the development of such tools, the authors conducted 6 focus group discussions with 12 primary school teachers and administrators to better understand the school climate around PA as well as school readiness to embrace PA tools that can be used during academic content learning. In addition, a pilot test of a new health promotion tool, the Jump In! educational response mat, was conducted with 21 second-grade students from one classroom in Northern Colorado in 2013. The results of both studies demonstrated acceptability and feasibility of incorporating PA into classroom learning, and suggested that tools like Jump In! may be effective at overcoming many of the PA barriers at schools. Teachers and administrators valued PA, believed that students were not getting enough PA, and were receptive to the idea of incorporating PA into classroom learning. Students who used Jump In! mats during a math lesson reported more interest in the class material and rated themselves as more alert during the lesson, compared to students who did not use the response mats. In addition, incorporating PA into the lesson did not impair performance on a quiz that assessed learning of the math content. Jump In! mats were successfully integrated into the lesson plan and were well-received by teachers and students. Together, the results of these studies suggest that, given the right tools, incorporating more PA into classroom learning may be beneficial and well-received by students, teachers, and administrators.